Kemampuan Numerasi Siswa dalam Menyelesaikan Masalah Kontekstual Materi Bentuk Aljabar Ditinjau Dari Kecerdasan Logis Matematis - Arma Sentia Lestari; Sri Subarinah; Tabita Wahyu Tri Utami (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This study aims to describe students’ numeracy skills in solving contextual problems on algebraic expressions based on their logical-mathematical intelligence. This research employed a descriptive qualitative method with subjects consisting of seventh-grade students at SMP Negeri 2 Mataram in the 2024/2025 academic year. Data were collected through a logical-mathematical intelligence test, a numeracy test consisting of two contextual essay questions, and in-depth interviews. The results show that students with high logical-mathematical intelligence demonstrate high numeracy skills, as indicated by their ability to use mathematical symbols and numbers accurately, analyze data in various forms, and draw logical conclusions. Students with moderate logical-mathematical intelligence have moderate numeracy skills—they can identify numerical information but still make calculation and interpretation errors. Meanwhile, students with low logical-mathematical intelligence show low numeracy skills, characterized by difficulties in understanding data, performing arithmetic operations, and interpreting results. These findings indicate a strong relationship between students’ logical-mathematical intelligence levels and their numeracy abilities in solving contextual problems involving algebraic expressions.